Considerations for Ku-Band Radar Retrieval of Snow Water Equivalent at Mid-Latitude Ontario Agricultural Sites. Issue 1 (2nd January 2021) - Thompson, Aaron; Kelly, Richard
Abstract: Mid-latitude snow is understudied compared to snow in the northern high latitudes despite its importance as a source of freshwater to this economically significant region. The mid-latitudes provide opportunity to understand the influence on SWE retrievals of ice and vegetation, conditions which may encroach the north with a warming climate. Successful retrieval of SWE and snow depth was demonstrated using the Microwave Emission Model of Layered Snowpacks, adapted for backscattering (MEMLS3&a) with multi-angle Ku-band UWScat snow observations (VV polarization), of agricultural fields in Maryhill and Englehart, Ontario. A single-layer parameterization provided best results for Maryhill (RMSE of 21.9 mm SWE) while a dual-layer parameterization provided best results for Englehart (RMSE of 24.6 mm). Accounting for soil effects using a soil-subtraction method improved RMSE by up to 6.3 mm SWE. Retrievals were repeated with in situ snow depths improving accuracy at both sites (RMSE = 12.0 and 10.9 mm SWE for Maryhill and Englehart, respectively). Observations containing ice lenses and partially buried vegetation yielded a retrieval accuracy of RMSE = 60.4 mm which improved with in situ snow depths (RMSE = 21.1 mm SWE). These results compared favorably with the often-cited accuracy requirement of RMSE = 30 mm SWE.